2005
DOI: 10.1093/carcin/bgi360
|View full text |Cite
|
Sign up to set email alerts
|

RAD50 and NBS1 are breast cancer susceptibility genes associated with genomic instability

Abstract: The Mre11 complex, composed of RAD50, NBS1 and MRE11, has an essential role in the maintenance of genomic integrity and preventing cells from malignancy. Here we report the association of three Mre11 complex mutations with hereditary breast cancer susceptibility, studied by using a case-control design with 317 consecutive, newly diagnosed Northern Finnish breast cancer patients and 1000 geographically matched healthy controls (P = 0.0004). RAD50 687delT displayed significantly elevated frequency in the studied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
139
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 182 publications
(145 citation statements)
references
References 26 publications
4
139
2
Order By: Relevance
“…Interestingly, an association between a specific lowpenetrance mutation of RAD50 and susceptibility to hereditary breast cancer has been reported recently, and mutation carriers show increased spontaneous chromosomal aberrations in their peripheral blood T lymphocytes (38), consistent with the role of MRN in maintaining genomic stability. In a recent study which looked for mutation in the consensus coding sequences of 13,023 genes in breast cancer tumor tissue, Mre11 was identified as one of the hotspots of mutation (39).…”
Section: Discussionmentioning
confidence: 56%
“…Interestingly, an association between a specific lowpenetrance mutation of RAD50 and susceptibility to hereditary breast cancer has been reported recently, and mutation carriers show increased spontaneous chromosomal aberrations in their peripheral blood T lymphocytes (38), consistent with the role of MRN in maintaining genomic stability. In a recent study which looked for mutation in the consensus coding sequences of 13,023 genes in breast cancer tumor tissue, Mre11 was identified as one of the hotspots of mutation (39).…”
Section: Discussionmentioning
confidence: 56%
“…For example, variants of DNA repair genes have been shown to confer breast cancer susceptibility via genomic instability (e.g., RAD50 and NBS1; ref. 38).…”
Section: Discussionmentioning
confidence: 99%
“…40 Similar to former reports on breast cancer families carrying mutations in ATM, CHEK2 or BRIP1, 37,38,51, 54 Rahman et al 40 reported that only two of four first-degree breast cancer-affected relatives of breast cancer probands with PALB2 mutations also carried the PALB2 mutations, indicating an incomplete segregation of PALB2 mutations with breast cancer and thereby mirroring the difficulties of screening these genes in breast cancer families when unaffected women ask for predictive molecular testing to specify their individual breast cancer risk. In addition, ATM, BRIP1, CHEK2 and 41 identified the Finnish founder mutation 687delT, which is associated with an increased breast cancer risk (odds ratio 4.3) in the Finnish cohort (n ¼ 317). But, subsequent analyses in additional cohorts from Sweden, Norway and Iceland (n ¼ 512) failed to identify the mutation, thus again indicating the high frequency of certain mutations in distinct populations that has to be considered if molecular screening is discussed.…”
Section: Breast Cancer Susceptibilitymentioning
confidence: 99%